PENGARUH MODEL PBL TERHADAP KEMAMPUAN BERPIKIR KRITIS KELAS IV SEKOLAH DASAR - Permatasari, Anggun Dwi; Satianingsih, Rarasaning (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is driven by the limited critical thinking abilities observed among pupils. It seeks to examine whether the PBL approach has an impact on critical thinking skills in relation to the topic of Changes in the States of Matter in Year 4 at SDN Dukuh Menanggal I/424 Surabaya. The research employs a quantitative approach with an experimental method and a Quasi-Experimental Design. The population consists of Year 4 students at SDN Dukuh Menanggal I/424 Surabaya, with the sample comprising two classes: the experimental class (IVA), which applied the PBL model, consisting of 28 students, and the control class (IVB), which used the Project-Based Learning (PJBL) model, with 24 students. Data were collected through essay tests designed to measure critical thinking skills based on the indicators of analysing, problem-solving, and drawing conclusions. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing using a t-test. The findings revealed that hypothesis testing through an Independent Sample t-Test produced a significance value of 0.000 (<0.05). This result indicates a notable impact of the PBL approach on the development of critical thinking skills in the context of the topic Changes in the States of Matter for Year 4 pupils at SDN Dukuh Menanggal I/424 Surabaya.